Online Simultaneous Hydrogen/Deuterium Exchange of Multitarget Gas-Phase Molecules by Electrospray Ionization Mass Spectrometry Coupled with Gas Chromatography - Jeong, Eun Sook; Cha, Eunju; Cha, Sangwon; Kim, Sunghwan; Bin Oh, Han; Kwon, Oh-Seung; Lee, Jaeick (AMER CHEMICAL SOC, 2017)
In this study, a hydrogen/deuterium (H/D) exchange method using gas chromatography-electrospray ionization/mass spectrometry (GC-ESI/MS) was first investigated as a novel tool for online H/D exchange of multitarget analytes. The GC and ESI source were combined with a homemade heated column transfer line. GC-ESI/MS-based H/D exchange occurs in an atmospheric pressure ion source as a result of reacting the gas-phase analyte eluted from GC with charged droplets of deuterium oxide infused as the ESI spray solvent. The consumption of the deuterated solvent at a flow rate of 2 mu L min(-1) was more economical than that in online H/D exchange methods reported to date. In-ESI-source H/D exchange by GC-ESI/MS was applied to 11 stimulants with secondary amino or hydroxyl groups. After H/D exchange, the spectra of the stimulants showed unexchanged, partially exchanged, and fully exchanged ions showing various degrees of exchange. The relative abundances corrected for naturally occurring isotopes of the fully exchanged ions of stimulants, except for etamivan, were in the range 24.3-85.5%. Methylephedrine and cyclazodone showed low H/D exchange efficiency under acidic, neutral, and basic spray solvent conditions and nonexchange for etamivan with an acidic phenolic OH group. The in-ESI-source H/D exchange efficiency by GC-ESI/MS was sufficient to determine the number of hydrogen by elucidation of fragmentation from the spectrum. Therefore, this online H/D exchange technique using GC-ESI/MS has potential as an alternative method for simultaneous H/D exchange of multitarget analytes.